Electricity deficit cost estimation in Brazil by applying input-output analysis. - Martins, Lilian Maluf (2018)
The supply chain risk management discipline studies how to address daily and extraordinary risks to avoid vulnerability and to guarantee production continuity. In the case of the electricity sector, the economic impact of interrupting the power supply is depicted by an indicator called the deficit cost, measured in monetary unit per electricity consumption unit (for example, in Brazil, R$/MWh). This value is commonly applied to cost-benefit analysis that results in decisions about maintenance and investment in the electricity system in the medium and long term, in addition to composing the short-term energy price. Most countries in the world have a thermal energy matrix, and cases in which interruption problems occur are mainly due to punctual failures in generation or transmission and last a few hours or days until maintenance is concluded. Brazil, however, has been strongly dependent on hydrological conditions ever since the main generation source became hydroelectric. Since restricted energy supply scenarios last longer, from weeks to months, a better measure for the electricity structural deficit impact is the economic loss in the deficit-affected regional production, translated as the GDP (gross domestic product) region. This dissertation estimates the Brazilian GDP marginal loss due to power deficits by applying an input-output (I/O) matrix analysis methodology and concludes that the officially adopted deficit cost is underestimated.